EOSINOPHILIA IN EXPERIMENTAL FASCIOLIASIS IN GOATS INFECTED WITH SHEEP AND BUFFALO ISOLATES OF FASCIOLA ‎GYGANTICA - Y. Al-Kubaisee , R.; I. Altaif, K. (The Iraqi Journal of Veterinary Medicine, 1987)
Twenty one male goats 3-4 months of age were exposed to five metacercariae per kg. of body weight of two isolates of Fasciola gigantica obtained from sheep and buffalo. Eosinophilia was mostly marked after prepatency in goats infected with sheep isolate.